2017
DOI: 10.3390/mca22040043
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Neural Networks and ANFIS for Forecasting Attendance Rate of Soccer Games

Abstract: Abstract:The main purpose of this study was to develop and apply a neural network (NN) approach and an adaptive neuro-fuzzy inference system (ANFIS) model for forecasting the attendance rates at soccer games. The models were designed based on the characteristics of the problem. Past real data was used. Training data was used for training the models, and the testing data was used for evaluating the performance of the forecasting models. The obtained forecasting results were compared to the actual data and to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 49 publications
(37 reference statements)
0
46
0
3
Order By: Relevance
“…Villa et al, 2011;Winfree et al, 2004). I found only two studies that predict stadium attendance without relying on information that is not accessible before a game has started and both use artificial neural network models to forecast short-run soccer match attendance rates (Şahin & Erol, 2017;Strnad et al, 2017).…”
Section: Predicting Game Attendance and Determinants Of Demandmentioning
confidence: 99%
“…Villa et al, 2011;Winfree et al, 2004). I found only two studies that predict stadium attendance without relying on information that is not accessible before a game has started and both use artificial neural network models to forecast short-run soccer match attendance rates (Şahin & Erol, 2017;Strnad et al, 2017).…”
Section: Predicting Game Attendance and Determinants Of Demandmentioning
confidence: 99%
“…The researchers found that the performance of ANN is better than (LRM). Sahin and Erol (2017) conclude that ANFIS has an advantage over both Artificial Neural Network (ANN) and Fuzzy Inference Systems (FIS). In their study, a combination of both ANN and FIS (ANFIS) result in a better-developed method.…”
Section: Results Of Anfis For Estimated Peak Load Demandmentioning
confidence: 99%
“…It has been used in numerous applications and presentations of various fields (like mechanics, physics, economics, biology, industry and others) (e.g., [95][96][97][98][99][100][101][102][103][104][105], to name just a few recent). It has also been studied by other authors or compared with other neural networks (e.g., [103,106,107]). Its main advantage lies on the fact that it automatically adjusts the membership functions to our available data in order to achieve the best performance of our system.…”
Section: Why Anfismentioning
confidence: 99%